Baboon syndrome or symmetric intertriginal and flexible exanthemas associated with medicines. Review of clinical cases - Dmitry I. Trukhan (LLC "MEDIAFORMAT", 2023)
In 1984, Danish dermatologists described a skin eruption limited to the buttocks, with possible involvement of the intertriginous areas and flexion areas, and named this pattern the baboon syndrome. At the beginning of the 21st century, a new acronym SDRIFE (drug-associated symmetrical intertriginous and flexural exanthema) was proposed by Swiss dermatologists along with five characteristic diagnostic criteria. We searched the PubMed database for key terms: "baboon syndrome", "symmetrical drug-related intertriginous and flexural exanthema", "SDRIFE" from the time of the first publication (1984) to 04/30/2023. Found 120 descriptions of baboon syndrome or SDRIFE, which was slightly more common in men. An increase in the frequency of development with age was noted, 60% of cases were in patients older than 50 years. Geographically, more than half (52.4%) of cases are in Europe, predominantly in southern and western European countries, 20% in India and 16.2% in Asian countries. Attention is drawn to the variety of drugs that can cause the development of baboon/SDRIFE syndrome. Almost half - 59 cases (49.2%) of the 120 presented in the review are associated with antibiotics, 24 cases (20%) with antibiotics of the penicillin group. During the pandemic of a new coronavirus infection, SDRIFE cases have been described in patients with COVID-19 and after vaccination against COVID-19. The leading place in the diagnosis and treatment of SDRIFE belongs to the dermatologist. However, given the variety of culprit drugs, a doctor of any specialty can encounter SDRIFE in his practice.